2010
DOI: 10.1007/s11892-010-0140-4
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Islet Autotransplantation: Indication, Technique, and Outcome

Abstract: Chronic pancreatitis is a rare disease in childhood. However, when severe, a total pancreatectomy may be the only option to relieve pain and restore quality of life. An islet autotransplant performed at the time of pancreatectomy can prevent or minimize the postsurgical diabetes that would otherwise result from pancreatectomy alone. In this procedure, the resected pancreas is mechanically disrupted and enzymatically digested to separate the islets from the surrounding exocrine tissue, and the isolated islets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 36 publications
0
31
0
1
Order By: Relevance
“…Recently, it is demonstrated that severe histopathological changes were associated with lower islet yield for auto transplantation indicating greater islet destruction in severely inflamed and fibrotic pancreas [6,7]. On the other hand, islets that were autotransplanted into the liver via portal vein were found to have improved functions with time [8]. This suggests that islet autotransplantation early in the progression of symptomatic disease can retain b-cell function.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it is demonstrated that severe histopathological changes were associated with lower islet yield for auto transplantation indicating greater islet destruction in severely inflamed and fibrotic pancreas [6,7]. On the other hand, islets that were autotransplanted into the liver via portal vein were found to have improved functions with time [8]. This suggests that islet autotransplantation early in the progression of symptomatic disease can retain b-cell function.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the islet yield for many patients was moderate to high (4,830 -3,692 IEQ/kg), and these transplanted islets may contribute to better glycemic control. [1][2][3][4][5] The rationale for targeting a physiologic glucose range in our transplant recipients is to avoid hyperglycemia-induced b-cell loss. This concept is supported by a large body of animal studies as well as ongoing work in clinical islet transplant recipients at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical procedure of TPIAT was performed as previously described, 1 with minor modifications to the gastrointestinal reanastamosis. In brief, a TP, partial duodenectomy, Roux-en-Y duodenojejunostomy, choledochojejunostomy, and splenectomy were performed.…”
Section: Procedures Of Tpiatmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants underwent total pancreatectomy as previously described [28][29][30] along with infusion of the patient's own islet cells into a tributary of the portal vein, or if elevated portal pressures prevented infusion of all the islets intraportally, the remaining islets were transplanted into the peritoneal cavity. Immediately after surgery, all patients were started on a continuous intravenous (IV) insulin infusion protocol with the goal of maintaining BG in the range of 80-125 mg/dL.…”
Section: Total Pancreatectomy and Islet Autotransplantation Proceduresmentioning
confidence: 99%